SOSIALISASI BAGI UMKM SARUNG TENUN TRADISIONAL TERHADAP HAK ATAS KEKAYAAN INTELEKTUAL DI KECAMATAN WABULA KABUPATEN BUTON - L. M. Ricard Zeldi Putra; Mashendra; Tarno Tarno; Ernawati Ernawati; Safrin Edy (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service aims to provide knowledge and understanding of Intellectual Property Rights for UMKM actors in Buton Regency. Micro, Small and Medium Enterprises (UMKM) have a very important role in encouraging the increase in the pace of the creative economy in the real sector of a nation, and are able to increase income for the community. Moreover, if it is added to the UMKM products, they already have intellectual property rights legally in their protection. The benefits of the role of Intellectual Property by business actors for UMKM products in Buton Regency so far have not been maximized, this is due to a lack of understanding in the community that the importance of Intellectual Property Rights as a form of legal protection from business competition over copyright claims so that there are still many UMKM products not yet available. registered as an example of a woven sarong product in the district of Wabula, Buton Regency. So in this service the need for socialization. In this socialization, several UMKM in traditional weaving sarongs were involved in Buton Regency